Boosting anode kinetics in vanadium flow batteries with catalytic bismuth nanoparticle decorated carbon felt via electro-deoxidization processing. Issue 16 (3rd April 2023) - Zhang, Qi-an; Yan, Hui; Song, Yuanfang; Yang, Jing; Song, Yuxi; Tang, Ao
Abstract : An electro-deoxidization processing strategy is reported to fabricate catalytic bismuth nanoparticle decorated carbon felt for high-performance vanadium flow batteries. Abstract : Vanadium flow batteries (VFBs) have proven to be an ideal candidate for long-duration grid-scale energy storage. However, high power operation of VFBs is still impeded by the intrinsically sluggish kinetics of V 2+ /V 3+ redox reactions at the anode. Herein, we design catalytic bismuth nanoparticle dispersed carbon felt via facile one-step electro-deoxidization processing, which enables significantly enhanced anode redox kinetics for high-performance VFB operation. Experimental analyses together with theoretical calculations show that bismuth nanoparticles are successfully dispersed on carbon fibers via electro-deoxidization of bismuth oxide in alkaline solutions with an optimized loading content and applied voltage, which subsequently prove effective in catalyzing V 2+ /V 3+ redox reactions and thus significantly boost anode kinetics. First-principles calculation further unravels that the electrocatalytic effect of bismuth on V 2+ /V 3+ redox reactions is essentially attributable to both desirable vanadium adsorption/desorption and intensified d–p orbital hybridization between vanadium 3d and bismuth 6p orbitals that delicately modulate the surface electronic state and facilitate interfacial charge transfer. Consequently, the full VFB cell adopting bismuth nanoparticle decorated carbon felt at the anode acquires a significantly enhanced VE of 73.4% at 400 mA cm −2 and a highly stable EE of 73.6% at 350 mA cm −2 over 450 charge–discharge cycles.